The determinants of effective Islamic lifestyle in achieving brand equity: a case study at Chinese Muslim food restaurants in Selangor / Muhammad Abd Hakim Abu Bakar and Rafizah Mohd Lazi - Abu Bakar, Muhammad Abd Hakim; Mohd Lazi, Rafizah (Faculty of Business and Management, 2014)
The title of this research study is “The Determinants of Effective Islamic Lifestyle In Achieving Brand Equity: A Case Study at Chinese Muslim Restaurants in Selangor”. The main purpose of this study is to determine the relationships between independent and dependent variables. There are three independent variables involved in this research which are Islamic product, Islamic promotion, Islamic ethics while the dependent variable is brand equity. In order to complete this research study, the hypothesis was constructed and focused on the objective to determine whether there has a significant relationship between those independent variables with brand equity. A total of 153 respondents have participated in this study. The methodology used for the research was primary and secondary data collection. For primary data, the researcher used questionnaire, observation and focus group interview with the person in charge at the restaurants. While for secondary data, the researcher gather and collect information from journals, articles and also official websites. Thus, the result was obtained through the analyzing and interpreting the data. The frequency analysis, reliability analysis, descriptive analysis and Pearson’s Correlation Analysis was used for data analysis. From the correlation analysis, found that those three independent variables have a significant, strong and positive relationship with the dependent variable. Thus, as conclusion there are clear shown that these three hypothesis which included Islamic product, Islamic promotion and Islamic ethics is supported.